2015
DOI: 10.1590/1519-6984.11713
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian scientific production on phytoplankton studies: national determinants and international comparisons

Abstract: In this study, we determined the temporal trends of publications by Brazilian authors on phytoplankton and compared these trends to those of other Latin American countries as well as to the 14 countries ranking ahead of Brazil in terms of scientific publication. To do this, we investigated phytoplankton studies published in an international database (Thomson-ISI). The data showed that Brazil plays an important role among other Latin American countries in the publication of these studies. Moreover, the trend of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…Thus, this microcrustacean study came to add information to other Brazilian scientiometric studies in limnology (e.g., Thomaz et al, 2010;Melo et al, 2006;Padial et al, 2008;Nabout et al, 2015a) and help to emphasize the gaps and biases for researchers and policy makers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, this microcrustacean study came to add information to other Brazilian scientiometric studies in limnology (e.g., Thomaz et al, 2010;Melo et al, 2006;Padial et al, 2008;Nabout et al, 2015a) and help to emphasize the gaps and biases for researchers and policy makers.…”
Section: Discussionmentioning
confidence: 90%
“…In the early 2000's several scientiometric studies of limnological areas of Brazil were conducted (Thomaz et al, 2010;Melo et al, 2006;Padial et al, 2008;Nabout et al, 2015a), highlighting advances made since the 1970s and ongoing trends. In addition, a scientiometric study focused on climatic change has been recently reported (Nabout et al, 2012), as has a phytoplankton-based study (Carneiro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Only two Latin American countries (Brazil and Mexico) were among the top ten in national production. These two countries have been conspicuous in scientific production when compared with other Latin American countries (e.g., Nabout et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…An effective way to produce a systematic review on this subject is through a scientometric study, which allows a quantitative understanding of research trends (e.g. Carneiro et al, 2008;Alves et al, 2014;Nabout et al, 2015). With a systematic synthesis of eutrophication studies, scientists may be able to understand the state of the literature on aquatic entre 2001 e 2016.…”
Section: Introductionmentioning
confidence: 99%